Analisis Kemampuan Berpikir Kritis dan Keterampilan Memecahkan Masalah Pada Materi Laju Reaksi Menggunakan Pembelajaran Konstruktivistik - Daud Dakabesi; Tiwi Nur Astuti (Universitas Nusa Cendana, 2025)
The purpose of this study is to analyze the development of critical thinking skills and problem-solving skills of students on the material of speed when implementing constructivist learning. This study is a quasi-experimental study type using a posttest only design research design. The sample selection used a random sampling technique that obtained a sample of 127 students of class XI MIPA who were then divided into two research classes, namely experimental class 1 and experimental class 2. Both research classes will be applied constructivist learning model with details, experimental class 1 applies the problem-based learning (PBL) model while experimental class 2 applies the guided inquiry learning model. Data collection was obtained from research instruments in the form of critical thinking ability tests, problem-solving skills tests, critical thinking ability questionnaires and problem-solving skills observation sheets. The statistical test used to analyze the data was the MANOVA test with a significance level of 5%. The findings of this study illustrate that students' critical thinking abilities and problem-solving skills increase when constructivist learning is implemented. However, the increase in these abilities and skills was not the same for both research classes.